Solution of a countable system of quasilinear partial differential equations multiperiodic in a part of variables - Berzhanov, A. B.; Kurmangaliev, E. K. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We establish sufficient conditions for the existence and uniqueness of solutions of a countable system of first-order quasilinear partial differential equations multiperiodic in a part of variables.